Rice Bran Derived Bioactive Compounds Modulate Risk Factors of Cardiovascular Disease and Type 2 Diabetes Mellitus: An Updated Review - Saji, Nancy; Francis, Nidhish; Schwarz, Lachlan J.; Blanchard, Christopher L.; Santhakumar, Abishek B. (Nutrients, 2019)
Cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) are two chronic diseases that have claimed more lives globally than any other disease. Dietary supplementation of functional foods containing bioactive compounds is recognised to result in improvements in free-radical-mediated oxidative stress. Emerging evidence indicates that bioactive compounds derived from rice bran (RB) have therapeutic potential against cellular oxidative stress. This review aims to describe the mechanistic pathways behind CVD and T2DM development and the therapeutic potential of polyphenols derived from RB against these chronic diseases.